Renoprotective Effect of Orthosiphon stamineus Benth. Leaves Extract Against Renal Histological Damage on Mice (Mus musculus) Induced by Reheated Palm Oil - Setiawan, Candra Aji; Widjokongko, Bambang; Utari, Siti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Orthosiphon stamineus Benth. contains active substances polyphenols which are predominantly in the leaves. Polyphenols are capable to reduce oxidative stress dan halt lipid peroxidation on renal cells because of its antioxidant properties. Palm oil is widely used in Indonesia. It is known that reheated palm oil can damage renal cells by inducing lipid peroxidation reaction. The objective of this study is to know renoprotective effect of Orthosiphon stamineus Benth. to inhibit damage to the renal cells of mice (Mus musculus) induced by reheated palm oil. Methods: This study was an experimental laboratory with a post test only controlled group design. Samples were male Swiss-Webster mice, 2-3 months old and Â± 25 g in weight, taken as many as 25 heads by incidental sampling and divided into 5 groups randomly. For 14 days, the Negative Control Group (KK (-)) were given aquadest, the Positive Control Group (KK (+)) were given reheated palm oil, and Treatment Group 1-3 (KP1-3) ââwere given reheated palm oil and Orthosiphon stamineus Benth. leaves extract with multilevel dose 3.5 mg, 7 mg, and 14 mg. On day 15, mice were terminated and the kidneys were made ââpreparations by the method of Paraffin Blocks and HE staining. Kidney histological features assessed by the sum of proximal tubular cells that undergo pyknosis, karyorhexsis, and karyolysis. Data were analyzed using the Kruskall-Wallis test (Î± = 0.05) and post hoc test of Mann-Whitney (Î± = 0,05). Results: Kruskal-Wallis test results showed a significant difference among the five study groups p = 0.000 (p < 0,05). Mann-Whitney test results showed significant differences between KK (-) - KK (+), KK (-) - KP1, KK (-) - KP2, KK (-) - KP3, KK (+) - KP1, KK (+ ) - KP2, KK (+) - KP3, KP1 - KP2, KP2 - KP3 (p < 0,05) and a non-significant difference between KP1 - KP3 (p < 0,05). Conclusions: Leaves extract of Orthosiphon stamineus Benth. have renoprotective effects on renal histological damage of mice (Mus musculus) induced by reheated palm oil. Keywords: Orthosiphon stamineus Benth. leaves extract, reheated palm oil, renal histological damage.Â